Chemical composition, antioxidant and antiproliferative activities of essential oil from rhizome and leaves of Curcuma mutabilis Škorničk., M. Sabu & Prasanthk., endemic to Western Ghats of India. Issue 16 (17th August 2020) - Soumya, T.; Jayasree, P. R.; Deepak, M.; Manish Kumar, P. R.
Abstract: Hydro-distilled essential oils, from fresh rhizomes and leaves of Curcuma mutabilis Škorničk., M.Sabu & Prasanthk., characterized by GC–MS revealed the presence of thirty three and twenty three compounds therein respectively. Whilst estrone methyl ether (3-Methoxyestra-1, 3, 5(10)-trien-17-one) was the major component in rhizome oil (47.35%), sesquiterpene hydrocarbons predominated as the major group (63.92%) in leaf oil with a higher preponderance of β-caryophyllene (25.48%), β-farnesene (19.47%) and α-humulene (11.01%). Weak antioxidant activities observed in these oils determined by DPPH and ABTS methods were apparently influenced both by the oil composition and the assay conditions. Rhizome oil showed higher antiproliferative activity than leaf oil against leukemic K562 (IC50 -6.8µg/mL) and colorectal HCT116 (IC50 -8.5µg/mL) cancer cell lines. This first report reveals composition and biological activities of essential oils from C. mutabilis . Graphical Abstract: